The Effect of Improvement Surrounding Soil on Driven Pile Friction Capacity - Abdulaziz Abdul Rassol Aziz (مجلة النهرين للعلوم الهندسية, 2017)
There is very close relation between the pile  capacity and surrounding soil conditions . In cohesionless soil the pile effected on surround soil by compact loose ,cohesionless deposits through a combination of pile volume displacement and driving  vibrations .the pile foundation usually designed to exceed the weak soil to the firm deposit .in this study we shall try to improve the  weak soil surround the pile and observe the effect  of improvement on pile capacity for driven pile.